2008
DOI: 10.1016/j.indmarman.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sales force automation systems: An analysis of factors underpinning the sophistication of deployed systems in the UK financial services industry

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In reality, however, adoption is also commonly initiated as a mimetic movement rather than a result of rational and strategic thinking (Wright, Fletcher, Donaldson, & Lee, 2008). Erffmeyer and Johnson (2001) reveal that a typical purpose of having an automation technology is to automate as many things as possible.…”
Section: Organizational Adoption Of Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, however, adoption is also commonly initiated as a mimetic movement rather than a result of rational and strategic thinking (Wright, Fletcher, Donaldson, & Lee, 2008). Erffmeyer and Johnson (2001) reveal that a typical purpose of having an automation technology is to automate as many things as possible.…”
Section: Organizational Adoption Of Technologiesmentioning
confidence: 99%
“…This line of reasoning implies that adoption is driven by a managerial perception that there is intrinsic value in automating things. A lack of strategic planning may lead to an adoption process that focuses on technological capabilities rather than the required organizational changes (Campbell, 2003;Wright et al, 2008). Accordingly, Hillebrand, Kok, and Biemans (2001) show that mimetic moves in adoption decisions jeopardize the benefits of the technology investment.…”
Section: Organizational Adoption Of Technologiesmentioning
confidence: 99%
“…Essentially, what this means for marketers is unprecedented access to measurable results at any point in a campaign, providing timely insights on the behavior of potential customers along their journey, which in turn allows for adjustments and fine-tuning in real-time (Järvinen and Taiminen, 2016), with eventual realignments in strategic decisions. These results have been reported in different contexts, including the drug industry (Alsaad et al , 2018), wine tourism (Festa et al , 2020) and financial services (Wright et al , 2008), but there is still a scarcity of empirical research.…”
Section: Literature Reviewmentioning
confidence: 97%
“…A study, explored the organizational variables (information orientation and organization slack and control), strategic variables (strategic importance and integration) and linked with sophistication of SFA UK financial services firms. Authors found a positive correlation between Information Technology (IT) and marketing [6].…”
Section: A Adoption Of Sfa Systemmentioning
confidence: 99%